What influences prescribing decisions in a multimorbidity and polypharmacy context on the acute medical unit? An interprofessional, qualitative study. Issue 5 (12th December 2020) - Rivers, Peter H; Langford, Nigel; Whitehead, Andrew; Harrison, Tim
Abstract: Rationale, aims and objectives: The primary aim of the study was to understand the mindset of doctors and pharmacists, as they embark upon prescribing in a multimorbidity and polypharmacy context during routine practice at a hospital acute admissions unit. The study also aimed to evaluate to what extent attitudes, embedded within real‐life decision‐making scenarios, relate to existing theory and models of prescribing decisions. Methods: Anonymized case studies were identified from the medical notes of patients aged 65 and over with conditions likely to be associated with multimorbidity, medication issues and polypharmacy: namely: fall, urinary tract infection, confusion or lower respiratory tract infection. A total of 39 doctors based on the acute medical admissions unit and 9 pharmacists were recruited to one of three focus groups. Patient case‐studies provided the context for discussion from which verbatim transcripts were thematically analyzed using an interpretative, qualitative approach. Sub‐themes were matched to Murshid and Mohaidin's proposed model of physician prescribing decisions. Results: Seven principal themes were identified that were associated with prescribing decisions on the acute medical unit, namely, "patient characteristics, " "drug characteristics, " "pharmacist factors, " "trustworthiness, " "reliability of medication history, " "competing priorities" and "responsibilities of prescribers." Conclusion: Prescribing decisions on the acute medical admissions unit were influenced by a variety of factors, some of which have already been acknowledged within existing theories and models. The findings provisionally offer new insights, which, subject to confirmation by further research, bring to light three attitudinal characteristics that may impact negatively upon the quality of prescribing decisions. These include, first, how perceived poor reliability of medication history may result in information gaps that compromise prescribing decisions; second, how competing priorities restrict doctors' aptitude to conduct a review of medication and finally, how doctors may rationalize the assignment of medication review to the GP.